ETOS KERJA MASYARAKAT DAWAN DAN KORELASINYA DENGAN KONSEP KERJA MENURUT KARL MARX (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
This article pays attention to description of metaphysical and practical meaning of wisdom expression “meup onle ate, tah onle usif”, a cultural philosophy. In addition, this article also wants to describe the relevance of these local wisdom expressions in dealing with the reality of life for a tribe on the island of Timor, namely the Dawan tribe. The expression of wisdom or philosophy is closely related to work ethic. The work ethic of the Dawanese is decreasing day by day for various reasons. The article also uses working concept from Karl Marx as a colaburation o get deep meaning. The methodology used in this article is a literature methodology combined with phenomenological studies. This article basically wants to reveal the noble values ??and operational values ??of the philosophy in question. By looking at these two kinds of values, the author wants to make readers aware, especially the Dawanese, to have will to work because the authors finds that work is not just a matter of looking for food, but more than that, there is a metaphysical dimension behind work activity. The distinctive contributions of this article are inspiration as well as motivation to work hard in everyday life.
Keywords: Dawanese; cultural philosophy; work; work ethic